Defence responses triggered during the plant-pathogen interaction between strawberry (Fragaria x ananassa) and Colletotrichum acutatum - Caro, Maria Del Pilar; Pott, Delphine M.; Tomas-Grau, Rodrigo H.; Perato, Silvia Marisa; Albornoz, Patricia Liliana; Díaz Ricci, Juan Carlos; Osorio, Sonia; Salazar, Sergio Miguel; Moschen, Sebastian Nicolas (Elsevier, 2023)
Strawberry (Fragaria x ananassa Duch.) production is an important economic activity in Argentina. Anthracnose, caused by Colletotrichum spp., is the most destructive fungal disease for strawberry and causes a huge economic loss every year. The gene-regulatory networks and metabolic pathways involved in the interaction between Fragaria ananassa and Colletotrichum acutatum are poorly understood. Sixteen strawberry cultivars were characterized in a local strain, M11, of C. acutatum, and the results showed that the Camarosa and Pajaro cultivars were the most tolerant and susceptible, respectively. Metabolic, biochemical and molecular analyses were used to study pathogen and strawberry interaction. The results showed that (1) after being infected by the pathogen, the Camarosa cultivar showed early induction of stomatal closure, callose and lignin accumulation; (2) the metabolic profile of the Camarosa cv. infected by C. acutatum showed high levels of carbohydrate accumulation, while the Pajaro cv. was characterized by accumulation of amino acids and their derivatives; (3) the expression of defence-related genes was induced earlier in the Camarosa cv. The above results demonstrated that an early and complex network of defence responses is triggered in the tolerant cultivar (Camarosa cv.), when infected by C. acutatum. Altogether, these results led us to expand the boundaries of knowledge of the metabolic pathways and gene-regulatory networks involved in the interaction between strawberry and Colletotrichum acutatum.